Factors Affecting Job Satisfaction in Educational Institutions Vis a Vis its Managerial Implication: Examining the Impact of Job Satisfaction on Employee Performance in Educational Institutions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Job satisfaction represents one of the most difficult areas faced by today’s employees in which it has a very large impact on the job satisfaction on the motivation of employees, while the level of motivation has an impact on performance of organization. The Satisfaction of employees depends on various intrinsic as well as extrinsic factors such as performance of employee, professional autonomy, pay, working conditions, and it is very important to pay attention towards the employees to make them satisfy. Satisfaction of employees is related with the performance of an individual, employee reward, quality of work life, etc. The study was conducted to check the Satisfaction level of employees in organizational activities whether these are curricular activities or non-curricular activities. The sample comprised of 60 employees from teaching as well as non-teaching departments of Chaudhary Ranbir Singh University, Jind. The scores were analyzed with the help of mean, S.D., t-test and ANOVA based on 5-scaled tool developed by the researcher itself. The results clearly pointed out that employee who are working in this organization are happy with their job and they it has found that satisfaction level of employees towards their job during engagement and after engagement is found high. The study also reveals that satisfaction level of employees’ concerned with financial compensation plays an important role in the performance of employees as well as organization.